Investigating Monoliths (Vinyl Azlactone-co-Ethylene Dimethacrylate) as a Support for Enzymes and Drugs, for Proteomics and Drug-Target Studies - Olsen, Christine; Skottvoll, Frøydis Sved; Brandtzaeg, Ole Kristian; Schnaars, Christian; Rongved, Pål; Lundanes, Elsa; Wilson, Steven Ray (Frontiers in Chemistry, 2019)
Prior to mass spectrometry, on-line sample preparation can be beneficial to reduce manual steps, increase speed and enable analysis of limited sample amounts. For example, bottom-up proteomics sample preparation and analysis can be accelerated by digesting proteins to peptides in an on-line enzyme reactor. We here focus on low-backpressure 100 µm inner diameter (ID) x 160 mm, 180 µm ID x 110 mm or 250 µm ID x 140 mm vinyl azlactone-co-ethylene dimethyacrylate (poly(VDM-co-EDMA)) monoliths as supports for immobilizing of additional molecules (i.e. proteases or drugs), as the monolith was expected to have few unspecific interactions. For on-line protein digestion, monolith supports immobilized with trypsin enzyme were found to be suited, featuring the expected characteristics of the material, i.e. low backpressure and low carry-over. Serving as a functionalized sample loop, the monolith units were very simple to connect online with liquid chromatography. However, for on-line target deconvolution, the monolithic support immobilized with a Wnt pathway inhibitor was associated with numerous secondary interactions when exploring the possibility of selectively trapping target proteins by drug-target interactions. Our initial observations suggest that (poly(VDM-co-EDMA)) monoliths are promising for e.g. on-line bottom-up proteomics, but not a “fit-for-all” material. We also discuss issues related to the repeatability of monolith-preparations.